Adverse effects of circadian desynchrony on the male reproductive system: an epidemiological and experimental study. Issue 7 (3rd July 2020) - Liu, Kun; Hou, Guizhong; Wang, Xiaogang; Chen, Huatao; Shi, Fuquan; Liu, Chang; Zhang, Xi; Han, Fei; Yang, Huan; Zhou, Niya; Ao, Lin; Liu, Jinyi; et al.
Abstract: STUDY QUESTION: Is circadian desynchrony a risk factor of male reproductive damage in semen parameters and/or reproductive hormones? SUMMARY ANSWER: Circadian desynchrony correlates with decrease of sperm count, which was improved when circadian desynchrony was attenuated. WHAT IS KNOWN ALREADY: Circadian desynchrony caused by work (shift work) and non-work-related reasons is prevalent worldwide and has been found to be associated with decreased female fertility, but whether it harms male reproductive health is unclear. STUDY DESIGN, SIZE, DURATION: A hybrid research was conducted. (i) A cross-sectional study of 1346 Chinese men in 2007 was used to analyze the association between semen/hormone biomarkers and work-related circadian desynchrony, which was divided into rotating shift work and permanent shift work against non-shift work. (ii) A cohort of 796 Chinese undergraduates from 2013 to 2014 was used to analyzed the association between semen/hormone biomarkers and non-work-related circadian desynchrony (between school days and days off). (iii) The biomarker identified simultaneously in both populations was further validated in male C57BL/6J mice housed under conditions simulating circadian desynchrony. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 17 semen/hormone biomarkers were compared among rotating shift workers and permanent shift workers against non-shift workers in the 1346 reproductive-age Chinese men. A total of 14 semen/hormone biomarker was analyzed in the undergraduate cohort for correlation with non-work-related circadian desynchrony (measured by Munich Chronotype Questionnaire) in 2013 and 2014 and compared between the 2 years. Photoperiod-shifting method was used to establish the mouse model, in which the biomarker was examined and molecular mechanism was explored by apoptosis analysis, DNA content analysis, transcriptome sequencing, real-time PCR and western blotting. MAIN RESULTS AND THE ROLE OF CHANCE: Among the semen/hormone biomarkers, sperm count was found to be lower in rotating shift workers, who had a higher risk of low sperm count defined by Chinese Ministry of Health (total sperm/ejaculate < 120 × 10 6 ) than non-shift workers (odds ratio = 1.26, 95% CI 1.05–1.52). This biomarker was replicated in the undergraduate cohort, where each hour of circadian desynchrony was associated with 1.16 (95% CI 1.02–1.31) fold odds of low sperm count, and sperm count increased during 2014 in men who reduced circadian desynchrony after 2013. A decrease of sperm count with circadian desynchrony and its recovery after removal of circadian desynchrony was also observed in the mouse model. During asynchrony, increased apoptosis was found in seminiferous tubules and the marker genes of post-spermatocyte stage cells were down-regulated. The most enriched functional pathway was homologous recombination, which happened during meiosis. LIMITATIONS, REASONS FOR CAUTION: The study of human beings was observational while the animal study has potential difference in circadian desynchrony exposure and species susceptibility. Further researches are needed to clarify the causal relationship in men. WIDER IMPLICATIONS OF THE FINDINGS: These findings provide novel insight to the effect of circadian desynchrony on male reproductive health and a potential strategy for prevention of reproductive damage. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the National Key R&D Program of China [2017YFC1002001] and National Natural Science Foundation of China [81871208]. There are no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: NA.